The Panorama of Mining in Peru. Interview with Hernán Torres Alvarez and Sergio Cueva Chauca - Cueva Chauca, Sergio (2015)
In this interview, the authors explain about the importance and current panorama of the mining activity in Peru, that has generated great benefits for this country. Furthermore, they discussed the major internal and external problems facing the mining industry in the country, and the ways in which these problems have been resolved through new laws. Finally, they give importance to the changes occurring in the international panorama, and that affect the internal mining industry of each country.